2023
DOI: 10.1186/s40468-023-00222-8
|View full text |Cite|
|
Sign up to set email alerts
|

Constraints in employing learning-oriented assessment in EFL classrooms: teachers’ perceptions

Abstract: Learning-oriented assessment has been called a practice that can be employed to increase the power of assessment practices in the classroom and one that has been said to promote efficient student learning. However, it is not always easy to employ learning-oriented assessment in English classes, because of a number of constraints. This study aimed at investigating the constraints which hinder teachers’ use of learning-oriented assessment in EFL classes. A phenomenological research method was used to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Following publication of the original article (Jalilzadeh & Coombe, 2023), the authors reported that the listed corresponding author was mistakenly assigned to Christine Coombe.…”
Section: Correctionmentioning
confidence: 99%
“…Following publication of the original article (Jalilzadeh & Coombe, 2023), the authors reported that the listed corresponding author was mistakenly assigned to Christine Coombe.…”
Section: Correctionmentioning
confidence: 99%
“…The design of effective assessment procedures should facilitate effective learning and pave the way for them to learn more. This is where giving feedback is a key component of quality assessment practices, which aim to promote student learning (Jalilzadeh & Coombe, 2023). The primary goals of assessment are to gauge and assess students' knowledge.…”
Section: Language Assessment and Its Significance Rolesmentioning
confidence: 99%
“…He proposed three major levels that influence teachers' understanding and practices in classroom settings: micro-level, mesolevel, and macro-level. With regard to quality language assessment practices, Jalilzadeh and Coombe (2023) identified several constraints of quality assessment that inhibit student learning, which could be categorized into three groups. They are teacher-related constraints, learner-related constraints, and institute-related constraints.…”
Section: Inhibitors Of Quality Assessment Practicesmentioning
confidence: 99%
See 2 more Smart Citations